THE COMMUNICATIVE POTENTIAL OF MUSICAL EXPRESSIVENESS - M. V. Alekseeva (Концепт: философия, религия, культура, 2019)
This article offers a brief overview of some challenges and paradoxes of contemporary research as well as various social questions related to them. Key problems of consciousness research are stated relating to the scientific work on artificial intelligence development. Due to such ambitious objectives of modern science, there is a special attention to personality sphere, to its emotional sufferings and personal creative aspirations. The proposed theses of research of the communicative and creative possibilities of the musical language, its qualitative differences from the considered potential of verbal semantics give a clear idea that the language of music is directly related to emotional expressiveness and cognitive process stimulation. As a result of such a summary, it becomes obvious that the study of verbal and musical expressive possibilities, their comparative analysis in the realities of cultural and communication tendencies of modernity is not limited to the needs of the sphere of art. The article also addresses communicative possibilities of musical expressiveness in light of the ability of music to convey the flow of personal emotions.The novelty of this article is to substantiate further detailed study of musical expression communication possibilities, which will make personal emotional world accessible, i.e. qualia. In turn, the status of qualia is considered as one of the most acute and widely discussed problems in modern philosophy, since representatives of various fields of science often see it as a key to understanding the nature of consciousness.